1990
DOI: 10.1115/1.2891172
|View full text |Cite
|
Sign up to set email alerts
|

On the Application of a Constitutive Equation for Whole Human Blood

Abstract: In consideration of the pulsatile blood flow in a conduit, the constitutive equation for the whole human blood of F. J. Walburn and D. J. Schneck (Biorheology, Vol. 13, 1976, pp. 201-210) is utilized. Governing equations are solved numerically yielding the velocity and the shear stress distributions. These results are discussed and compared with the Newtonian fluid, Casson's fluid, and Bingham fluid applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 0 publications
0
29
0
1
Order By: Relevance
“…Some studies found non-Newtonian rheology important (Rodkiewicz et al, 1990;Tu and Deville, 1996;Gijsen et al, 1999), while others found that it is relatively unimportant (Perktold et al, 1989;Ballyk et al, 1994), in determining flow patterns in large arteries. The paper of Ballyk et al (Ballyk et al, 1994) contains a good discussion of possible reasons for this discrepancy, particularly in light of their definition of the non-Newtonian importance factor.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies found non-Newtonian rheology important (Rodkiewicz et al, 1990;Tu and Deville, 1996;Gijsen et al, 1999), while others found that it is relatively unimportant (Perktold et al, 1989;Ballyk et al, 1994), in determining flow patterns in large arteries. The paper of Ballyk et al (Ballyk et al, 1994) contains a good discussion of possible reasons for this discrepancy, particularly in light of their definition of the non-Newtonian importance factor.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers indicated that the non-Newtonian behavior of the blood in great vessels has little influence on the local flow characteristics [6][7][8]. Nevertheless, other researchers [9][10][11] insist that it is of significant influence. In a word, the blood rheology has strong impact on the hemodynamics, and it is necessary to describe blood flow by proper non-Newtonian model.…”
Section: Introductionmentioning
confidence: 99%
“…Blood is non-Newtonian [12], [13] because of red blood cells. Investigation shows that at shear stress < 10 s -1 non-Newtonian behavior of blood becomes dominant.…”
Section: B Governing Equations and Boundary Conditionsmentioning
confidence: 99%